Anti-Corruption Culture as a Component of Organizational Culture - Зарічанський, Олег (Київський національний університет імені Тараса Шевченка, 2022)
The article reveals the psychological specificity of the organization's culture from the perspective of its perception of corruption. Anti-corruption culture is presented in the context of human relations through the prism of moral and immoral, proper and improper, good and evil, useful and harmful, legal and illegal, beautiful and ugly. It is noted that the anti-corruption culture, as opposed to the corruption culture, is studied as certain value guidelines aimed at the manifestation of an active citizen's position regarding corruption. We consider anti-corruption culture as a person's ability to consciously and morally resist corruption. Also, if you rely on the theory of contagion, you can imagine a model of the formation of a corruption subculture, where the value of one individual becomes the value of the group. The spread of both corrupt and other values within the group occurs as a result of the exchange of cultural samples through speech, behavior, clothing, and experience. Such an exchange continues unconsciously in the process of gaining experience and improving professional skills. The mechanisms by which the corruption subculture survives have been determined. The stages of its development in the organization are presented.It was noted that the main difference in the formation of the organizational anti-corruption culture is its development at the level of the philosophy and ideology of the organization, in strict control, as well as in the improvement of the regulatory and legal framework; the anti-corruption culture must be clear and a priori, shared by all members of the organization; the anti-corruption culture of the organization can be formed through a clear, unambiguous and clear legal framework.At the same time, it should be noted that the anti-corruption culture of the organization consists of the culture of the profession and the actual anti-corruption culture of the organization.

Розкрито психологічну специфіку культури організації в ракурсі сприйняття нею корупції. Антикорупційну культуру представлено в контексті людських відносин крізь призму морального й аморального, належного та неналежного, добра і зла, корисного та шкідливого, правового й неправового, прекрасного та потворного. З'ясовано, що антикорупційну культуру, на противагу корупційній культурі, досліджено як певні ціннісні настанови, спрямовані на вияви активної громадянської позиції щодо корупції. Антикорупційну культуру розглянуто як здатність людини свідомо й морально протистояти корупції. З огляду на теорію зараження, можна уявити модель формування корупційної субкультури, де цінність одного індивіда стає цінністю групи. Поширення як корупційних, так й інших цінностей усередині групи відбувається унаслідок обміну культурними зразками через мовлення, поведінку, одяг, досвід. Такий обмін триває неусвідомлено у процесі набуття досвіду й удосконалення професійних навичок. Визначено механізми, за рахунок яких виживає корупційна субкультура. Представлено етапи її розвитку в організації. Визначено, що основною відмінністю формування організаційної антикорупційної культури є її опрацьованість на рівні філософії й ідеології організації, у жорсткому контролі, а також в удосконаленні нормативно-правової бази; антикорупційна культура має бути зрозумілою й апріорною, такою, що поділяється всіма членами організації; антикорупційна культура організації може бути сформована через чітку, однозначну та зрозумілу нормативно-правову базу. Водночас необхідно зазначити, що антикорупційна культура організації складається з культури професії та, власне, антикорупційної культури організації.
Антикорупційна культура як складова культури організації
Keywords: антикорупційна культура; організація; корупція; цінності; психолого-правові механізми; anti-corruption culture; organization; corruption; values; psychological and legal mechanisms